2012
DOI: 10.1029/2011gb004118
|View full text |Cite
|
Sign up to set email alerts
|

CO2 semiannual oscillation in the middle troposphere and at the surface

Abstract: [1] Using in situ measurements, we find a semiannual oscillation (SAO) in the midtropospheric and surface CO 2 . Chemistry transport models (2-D Caltech/JPL model, 3-D GEOS-Chem, and 3-D MOZART-2) are used to investigate possible sources for the SAO signal in the midtropospheric and surface CO 2 . From model sensitivity studies, it is revealed that the SAO signal in the midtropospheric CO 2 originates mainly from surface CO 2 with a small contribution from transport fields. It is also found that the source for… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
14
0

Year Published

2013
2013
2018
2018

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 21 publications
(19 citation statements)
references
References 27 publications
3
14
0
Order By: Relevance
“…However, CO 2 is still emitted to the atmosphere by respiration from the biosphere in winter, which has a relatively sharp peak compared with the photosynthesis term. Thus the combination of gross primary production and respiration leads to the double peaks in each year in the net ecosystem production, which contributes to the semi-annual oscillation in CO 2 (Jiang et al, 2012). The semi-annual oscillation in the background signal is consistent with this interpretation.…”
Section: Average Seasonal and Semi-annual Patternssupporting
confidence: 75%
See 1 more Smart Citation
“…However, CO 2 is still emitted to the atmosphere by respiration from the biosphere in winter, which has a relatively sharp peak compared with the photosynthesis term. Thus the combination of gross primary production and respiration leads to the double peaks in each year in the net ecosystem production, which contributes to the semi-annual oscillation in CO 2 (Jiang et al, 2012). The semi-annual oscillation in the background signal is consistent with this interpretation.…”
Section: Average Seasonal and Semi-annual Patternssupporting
confidence: 75%
“…In contrast, the background data reflect global patterns with a drawdown in CO 2 during the summer growing season in the Northern Hemisphere. Jiang et al (2012) concluded that the semi-annual oscillation at NOAA's GLOBAL-VIEW sites is due to the combination of gross primary production and respiration of the biosphere. During the winter season, photosynthesis is largely reduced.…”
Section: Average Seasonal and Semi-annual Patternsmentioning
confidence: 99%
“…The harmonic functions include an annual seasonal cycle and semi-annual seasonal cycle [56]. We fit Equation (1) to the five-year time series of GM-XCO 2 .…”
Section: Calculation Of Seasonal Cycle Amplitude Of Xcomentioning
confidence: 99%
“…In addition to the trend [1][2][3] and the annual cycle [4][5][6][7][8][9], atmospheric CO 2 also demonstrates a lot of intra-seasonal [10,11] and inter-annual variability [12][13][14][15]. During the pre-satellite era, CO 2 analyses mainly utilized in-situ CO 2 measurements to investigate CO 2 variability, which is limited in space.…”
Section: Introductionmentioning
confidence: 99%